TLR2, TLR3, TLR4 and CD14 gene polymorphisms associated with oral lichen planus risk. (9th August 2013) - Stanimirovic, Dragan; Zeljic, Katarina; Jankovic, Ljiljana; Magic, Marko; Hadzi‐Mihajlovic, Milos; Magic, Zvonko
Abstract : The aim of this study was to assess whether polymorphisms in toll‐like receptor ( TLR ) and cluster of differentiation 14 ( CD14 ) genes are associated with oral lichen planus (OLP) risk and clinical course of the disease. The study group consisted of 101 patients with confirmed OLP and 104 healthy blood donors without systemic or oral mucosal diseases. Single nucleotide polymorphisms of TLR2 (rs3804099), TLR3 (rs3775291 and rs5743312), TLR4 (rs4986790 and rs4986791), and CD14 (rs2569190) genes were genotyped using real‐time PCR or PCR‐restriction fragment length polymorphism (PCR‐RFLP). The rs5743312 TLR3 gene polymorphism was associated with increased OLP risk in comparison with the wild type genotype (OR = 15.984, P  =   0.011). No association with OLP risk was observed for the polymorphisms studied in TLR2, TLR4 and CD14 genes or for the rs3775291 polymorphism of the TLR3 gene. The polymorphisms of the TLR3 gene were in linkage disequilibrium ( D ′ = 1, r 2   =   0.1). Identified haplotypes were not associated with the risk of OLP. The findings of the current study suggest that the TT genotype of the rs5743312 TLR3 gene polymorphism may play a significant role in the aetiology of OLP.